Inflammatory osteoarthritis of the hand - Punzi, Leonardo; Frigato, Marilena; Frallonardo, Paola; Ramonda, Roberta (Best practice & research. Clinical rheumatology, 2010)
Inflammatory or erosive are terms used interchangeably to define a clinical subset of osteoarthritis of the hand (HOA), targeting interphalangeal joints and characterised by an abrupt onset, marked pain and functional impairment, inflammatory symptoms and signs, including stiffness, soft tissue swelling, erythema, paraesthesiae, mildly elevated C-reactive protein and a worse outcome than non-erosive HOA. This subset is defined radiographically by subchondral erosion, cortical destruction and subsequent reparative change, which may include bony ankylosis. Although the presence of both clinical and radiographic aspects are very suggestive for the diagnosis in most cases, doubts have been recently raised from some studies which, by means of sensitive imaging techniques such as magnetic resonance imaging (MRI) and sonography, had found erosive changes in most patients with HOA, including those without signs of erosions at conventional radiography. However, many findings suggest that subjects with erosive HOA exhibit more inflammatory features than those with non-erosive HOA in different ways, including clinical, laboratory and sonographic aspects. Thus, it is probably preferable to use the double term inflammatory/erosive to better define this particular subset of HOA.